Avaliação in vitro do potencial antibacteriano do extrato da Aristolochia esperanzae Kuntze (Aristolochiaceae) sobre microrganismos bucais - Botelho Filho, Carlos Roberto (2019)
Aristolochia esperanzae Kuntze (Aristolochiaceae) is a plant of Brazilian flora little studied in the dental area but used in Indian integrative therapies to treat rheumatoid arthritis, menstrual symptoms and even weight loss. The aim of this in vitro study was to evaluate the antibacterial activity of this plant on specific oral microorganisms and their minimum inhibitory concentration. The microorganisms selected for the tests were Streptococcus mutans, Porphyromonas gingivalis and Enterococcus faecalis, which are the main bacteria linked to oral caries, periodontal disease and endodontic infection respectively. Plant material was collected on private property in the region of Curitiba, PR, Brazil. Harvesting was performed on three individuals at random from both leaves and stem. After collection the material was selected and separated for mechanical maceration. The essential oil (EO) and hydrolate, aqueous extracts of A. esperanzae, were obtained by cycles in the Clevenger hydrodistillation apparatus and subsequently frozen until testing. The EO was diluted with dimethyl sulfoxide (DMSO. The tests performed were: diffusion on agar with isolated bacteria and minimum inhibitory concentration (MIC). The agar diffusion was performed by CLSI disc-diffusion technique. All test preparation was performed in laminar flow to avoid risks of contamination. For both, the positive control was 0.12% chlorhexidine; for negative control 0,9% sodium chloride (NaCl) was used. In the first tests performed DMSO was used as a solvent control group. The results obtained in both tests for the three bacterial groups were negative for the extracts used, while the disk with the positive control obtained positive results as expected. The tests were repeated to prove reproducibility of results. In conclusion, these results suggest that A. esperanzae Kuntze had no antibacterial effect when tested against the oral microorganisms selected here.